Village Owned Enterprise Financial System Management - Fifi Nurafifah Ibrahim (Advances in Community Services Research, 2023)
In order to make the BUMDes program successful, the community service activity team, the Accounting Department of the UMI Faculty of Economics and Business, held a community service activity entitled Management of the Financial System of Timbuseng Village-Owned Enterprises, Patalassang District, Kab. The results achieved after this activity were increasing the knowledge of village officials and BUMDes officials (BUMDes chairmen and members/staff) regarding how to manage finances in terms of recording accurate, transparent and accountable budget items. The service team also provides hands-on training in the form of case examples and solutions related to the financial management of Village-Owned Enterprises to the community, especially village officials who manage BUMDes. This training process was also carried out by sharing and discussing the problems faced by partners and the service team immediately responded by providing solutions related to the obstacles encountered. From the results of guidance and counseling to partners regarding increasing understanding and knowledge about BUMDes governance, it appears that the partners have maximized results. This is because the information that partners have so far obtained is minimal and there has even been a mistake in the special management of recognition and in terms of legal entities so that through guidance and counseling, accurate information is provided for partners.